Building a world-class civil service for twenty-first century India - Das, S. K., 1945- (Oxford : Oxford University Press, 2010)
This monograph identifies a range of initiatives for reforming the civil services in India from a comparative perspective. The reform experiences of countries like the UK, Sweden, and New Zealand are analysed and modulated to suit India's requirements.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Public administration -- India; Civil service reform -- India